The Effect of Mass Fraction of Rice Straw Fiber on The Mechanical Properties and Water Absorption of Cassava Starch Biocomposite - Robertoes Koekoeh Koentjoro Wibowo; Sumarji; Hauzan Nafis Robbani (International Journal of Integrated Engineering, 2025)
The massive use of plastic packaging has a detrimental impact on the environment. Alternative solutions are needed, such as replacing plastic with biocomposites. In this study, biocomposites were made from rice straw fiber and cassava starch using the solution casting method. The mass fraction of rice straw fiber was varied at 74%, 78%, 82%, 86%, and 90%. To determine the characteristics of the biocomposites, tensile testing, bending testing, water absorption testing, macro observation, and Scanning Electron Microscope (SEM) observation were conducted. The results showed that as the mass fraction of rice straw fiber increased, the mechanical properties of the biocomposites decreased and water absorption increased. The ultimate tensile strength, tensile modulus, and elongation at break in the tensile test decreased by 79.95%, 66.65%, and 40.45%, respectively. The bending test results showed a decrease in flexural strength and flexural modulus by 78.53% and 70.37%, respectively. The water absorption test results showed an increase in water absorption by 49.1%. Macro and SEM fracture morphology observations revealed the presence of voids, agglomeration, and fibers pulled out of the matrix due to weak interfacial bonding, which caused the low mechanical properties and high water absorption. This study also compared rice straw fiber/cassava starch biocomposites with commercial egg tray samples. The results indicated that rice straw fiber/cassava starch biocomposites have superior mechanical properties and lower water absorption, suggesting their potential use as biocomposite packaging products.